Aplikasi E-Posyandu untuk Pendataan Ibu Hamil dan Bayi Berbasis Website pada Posyandu Teratai Kelurahan Wangga - Katrina Malo; Rambu Yetti Kalaway (Syntax Idea)
Posyandu Teratai, located in Wangga Village, East Sumba Regency, was established in July 1989 led by the cadre leader with the support of four cadres. This Posyandu faces challenges in the process of recording pregnant women and babies because it still uses books as the main media. The high number of visitors worsens the situation, resulting in limited data storage capacity, wasted time, risk of recording errors, and less than optimal analysis and monitoring of visit data. This study aims to design and build an Application for recording pregnant women and babies' visits, which is useful for simplifying the data management process, reducing recording errors, and increasing time efficiency and quality of service at Posyandu Teratai. Application development is carried out using the waterfall method, which is a systematic and structured approach to software development. This method includes the stages of needs analysis to deeply understand user and system needs, system design to design the architecture and application interface, implementation to realize the design into program code, testing to ensure the application functions according to specifications.